VPS13C-associated Parkinson's disease: Two novel cases and review of the literature. (January 2022) - Monfrini, Edoardo; Spagnolo, Francesca; Canesi, Margherita; Seresini, Agostino; Rini, Augusto; Passarella, Bruno; Percetti, Marco; Seia, Manuela; Goldwurm, Stefano; Cereda, Viviana; Comi, Giacomo P.; Pezzoli, Gianni; et al.
Abstract: VPS13C is a protein-coding gene involved in the regulation of mitochondrial function through the endolysosomal pathway in neurons. Homozygous and compound heterozygous VPS13C mutations are etiologically associated with early-onset Parkinson's disease (PD). Moreover, recent studies linked biallelic VPS13C mutations with the development of dementia with Lewy bodies (DLB). Neuropathological studies on two mutated subjects showed diffuse Lewy body disease. In this article, we report the clinical and genetic findings of two subjects affected by early-onset PD carrying three novel VPS13C mutations (i.e., one homozygous and one compound heterozygous), and review the previous literature on the genetic and clinical findings of VPS13C -mutated patients, contributing to the knowledge of this rare genetic alpha-synucleinopathy. Highlights: Biallelic VPS13C mutations are a definite genetic cause of monogenic Parkinson's disease (PD). Cognitive decline, dystonia, dysautonomia, and pyramidal signs may help to distinguish VPS13C -associated PD. We report two novel VPS13C -associated PD cases carrying three novel VPS13C pathogenic variants. Hearing impairment, oculomotor disturbances, and self-mutilating behaviour are novel phenotypic features.